The sum of a fraction and its reciprocal is $\dfrac{13}{6}$. Find the fraction if its numerator is 1 less than the denominator.
Answer
Verified
442.5k+ views
Hint: We are given that the numerator is one less than the denominator, thus we shall the numerator and denominator as two separate variables. We will then express the numerator variable in terms of the denominator variable and solve the quadratic equation thus formed by the factoring method.
Complete step by step solution:
Let the numerator of the fraction be $x$ and let the denominator of the fraction be $y$.
Given that sum of fraction and its reciprocal is $\dfrac{13}{6}$.
$\Rightarrow \dfrac{x}{y}+\dfrac{y}{x}=\dfrac{13}{6}$ ………….. (1)
We have also been given the relation that the numerator is 1 less than the denominator.
$\Rightarrow x=y+1$
Thus, the fraction formed is $\dfrac{x}{y}=\dfrac{y+1}{y}$. ………….. (2)
We shall make changes accordingly to equation (1) by substituting $x=y+1$.
$\Rightarrow \dfrac{y+1}{y}+\dfrac{y}{y+1}=\dfrac{13}{6}$
Taking LCM on the left-hand side of the equation, we get
$\begin{align}
& \Rightarrow \dfrac{y+1\left( y+1 \right)+y\left( y \right)}{y\left( y+1 \right)}=\dfrac{13}{6} \\
& \Rightarrow \dfrac{{{\left( y+1 \right)}^{2}}+{{y}^{2}}}{y\left( y+1 \right)}=\dfrac{13}{6} \\
\end{align}$
Using the algebraic property ${{\left( a+b \right)}^{2}}={{a}^{2}}+{{b}^{2}}+2ab$, we shall expand ${{\left( y+1 \right)}^{2}}$.
$\begin{align}
& \Rightarrow \dfrac{{{y}^{2}}+1+2y+{{y}^{2}}}{y\left( y+1 \right)}=\dfrac{13}{6} \\
& \Rightarrow \dfrac{2{{y}^{2}}+2y+1}{{{y}^{2}}+y}=\dfrac{13}{6} \\
\end{align}$
Cross-multiplying both sides with each other we get,
$\begin{align}
& \Rightarrow \left( 2{{y}^{2}}+2y+1 \right)6=13\left( {{y}^{2}}+1 \right) \\
& \Rightarrow 12{{y}^{2}}+12y+6=13{{y}^{2}}+13y \\
& \Rightarrow {{y}^{2}}+y-6=0 \\
\end{align}$
For any quadratic equation $a{{x}^{2}}+bx+c=0$,
the sum of the roots $=-\dfrac{b}{a}$ and the product of the roots $=\dfrac{c}{a}$.
Thus, for the equation, ${{y}^{2}}+y-6=0$, $a=1,$ $b=1$ and $c=-6$.
We will find numbers by hit and trial whose product is equal to $-6\times 1=-6$ and whose sum is equal to 1
Such two numbers are 3 and $-2$ as $3-2=1$ and $3\times -2=-6$.
Now, factoring the equation:
$\Rightarrow {{y}^{2}}+3y-2y-6=0$
Taking common, we get:
$\begin{align}
& \Rightarrow y\left( y+3 \right)-2\left( y+3 \right)=0 \\
& \Rightarrow \left( y-2 \right)\left( y+3 \right)=0 \\
\end{align}$
Hence, $y-2=0$ or $y+3=0$
On transposing the constant terms to the other side, we get
$\Rightarrow y=-3$ or $y=2$
Therefore, the roots of the quadratic equation are $y=-3,2$.
Substituting $y=2$ in equation (2), we get
$\dfrac{x}{y}=\dfrac{2+1}{2}$
$\Rightarrow \dfrac{x}{y}=\dfrac{3}{2}$
Therefore, the fraction is $\dfrac{3}{2}$.
Note: Another method of solving the quadratic equation formed was by first finding the discriminant of the equation and then calculating the roots by the predefined method as per given in algebraic mathematics.
Complete step by step solution:
Let the numerator of the fraction be $x$ and let the denominator of the fraction be $y$.
Given that sum of fraction and its reciprocal is $\dfrac{13}{6}$.
$\Rightarrow \dfrac{x}{y}+\dfrac{y}{x}=\dfrac{13}{6}$ ………….. (1)
We have also been given the relation that the numerator is 1 less than the denominator.
$\Rightarrow x=y+1$
Thus, the fraction formed is $\dfrac{x}{y}=\dfrac{y+1}{y}$. ………….. (2)
We shall make changes accordingly to equation (1) by substituting $x=y+1$.
$\Rightarrow \dfrac{y+1}{y}+\dfrac{y}{y+1}=\dfrac{13}{6}$
Taking LCM on the left-hand side of the equation, we get
$\begin{align}
& \Rightarrow \dfrac{y+1\left( y+1 \right)+y\left( y \right)}{y\left( y+1 \right)}=\dfrac{13}{6} \\
& \Rightarrow \dfrac{{{\left( y+1 \right)}^{2}}+{{y}^{2}}}{y\left( y+1 \right)}=\dfrac{13}{6} \\
\end{align}$
Using the algebraic property ${{\left( a+b \right)}^{2}}={{a}^{2}}+{{b}^{2}}+2ab$, we shall expand ${{\left( y+1 \right)}^{2}}$.
$\begin{align}
& \Rightarrow \dfrac{{{y}^{2}}+1+2y+{{y}^{2}}}{y\left( y+1 \right)}=\dfrac{13}{6} \\
& \Rightarrow \dfrac{2{{y}^{2}}+2y+1}{{{y}^{2}}+y}=\dfrac{13}{6} \\
\end{align}$
Cross-multiplying both sides with each other we get,
$\begin{align}
& \Rightarrow \left( 2{{y}^{2}}+2y+1 \right)6=13\left( {{y}^{2}}+1 \right) \\
& \Rightarrow 12{{y}^{2}}+12y+6=13{{y}^{2}}+13y \\
& \Rightarrow {{y}^{2}}+y-6=0 \\
\end{align}$
For any quadratic equation $a{{x}^{2}}+bx+c=0$,
the sum of the roots $=-\dfrac{b}{a}$ and the product of the roots $=\dfrac{c}{a}$.
Thus, for the equation, ${{y}^{2}}+y-6=0$, $a=1,$ $b=1$ and $c=-6$.
We will find numbers by hit and trial whose product is equal to $-6\times 1=-6$ and whose sum is equal to 1
Such two numbers are 3 and $-2$ as $3-2=1$ and $3\times -2=-6$.
Now, factoring the equation:
$\Rightarrow {{y}^{2}}+3y-2y-6=0$
Taking common, we get:
$\begin{align}
& \Rightarrow y\left( y+3 \right)-2\left( y+3 \right)=0 \\
& \Rightarrow \left( y-2 \right)\left( y+3 \right)=0 \\
\end{align}$
Hence, $y-2=0$ or $y+3=0$
On transposing the constant terms to the other side, we get
$\Rightarrow y=-3$ or $y=2$
Therefore, the roots of the quadratic equation are $y=-3,2$.
Substituting $y=2$ in equation (2), we get
$\dfrac{x}{y}=\dfrac{2+1}{2}$
$\Rightarrow \dfrac{x}{y}=\dfrac{3}{2}$
Therefore, the fraction is $\dfrac{3}{2}$.
Note: Another method of solving the quadratic equation formed was by first finding the discriminant of the equation and then calculating the roots by the predefined method as per given in algebraic mathematics.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.